2022
DOI: 10.1021/acsami.2c17231
|View full text |Cite
|
Sign up to set email alerts
|

Solid Migration to Assemble a Flower-like Nanozyme with Highly Dense Single Copper Sites for Specific Phenol Oxidation

Abstract: Nanozymes with high catalytic stability and sustainability have emerged as powerful competitors to natural enzymes for diverse biocatalytic applications. However, constructing a nanozyme with high specificity is one of their biggest challenges. Herein, we develop a facile solid migration strategy to access a flower-like single copper site nanozyme (Cu SSN) via direct transformation of copper foam activated by 2-methylimidazole. With highly clustered CuN3 sites whose local structure is similar to that of natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…The catalytic ability of L / D ‐Pen‐NFs is evaluated by the catalytic conversion of 4‐AP (4‐amino antipyrine) and 2,4‐DP (2,4‐dichlorophenol). [ 40 ] In the presence of O 2 , 2,4‐DP, and 4‐AP can generate a red product with a characteristic peak at 510 nm under the catalysis of L ‐Pen‐NF or laccase ( Figures a,b). The products catalyzed by L ‐Pen‐NFs display a deeper red color than those catalyzed by laccase (Figure S5a, Supporting Information), consistent with a higher absorption at 510 nm (Figure S5b,c, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The catalytic ability of L / D ‐Pen‐NFs is evaluated by the catalytic conversion of 4‐AP (4‐amino antipyrine) and 2,4‐DP (2,4‐dichlorophenol). [ 40 ] In the presence of O 2 , 2,4‐DP, and 4‐AP can generate a red product with a characteristic peak at 510 nm under the catalysis of L ‐Pen‐NF or laccase ( Figures a,b). The products catalyzed by L ‐Pen‐NFs display a deeper red color than those catalyzed by laccase (Figure S5a, Supporting Information), consistent with a higher absorption at 510 nm (Figure S5b,c, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Chen et al developed a flower-like single copper site (CuN 3 ) nanozyme (Cu SSN) with exceptional activity and specificity to oxidize phenols using solid migration. 114 When abundant CuN 3 was engaged, the specific activity of Cu SSN was found to be nine times greater than that of laccase, and it demonstrated remarkable stability even in challenging environmental conditions. Yang's group developed Cu SAs/CN nanozyme with active Cu-N 4 moieties, which exhibited comparable ascorbate POD (APX) mimetic activity and fast kinetic to natural APXs.…”
Section: Nanoscale Reviewmentioning
confidence: 99%
“…Such laccase mimic-based assays have also been developed for phenol sensing. [107][108][109][110][111][112][113][114][115][116][117][118][119][120][121][124][125][126][127][128] In a representative study, Liu's group synthesized a guanosine monophosphate (GMP) chelated Cu-based material and found that the material exhibited excellent laccase-mimicking activity. 121 They employed epinephrine as a laccase substrate and found that a colored oxidation product was formed (Fig.…”
Section: Detection Of Phenolic Pollutantsmentioning
confidence: 99%
“…[225][226][227] Recently, a lot of nanozyme catalytic systems have been developed to degrade phenolic pollutants. 107,[109][110][111][117][118][119]121,124,[228][229][230][231][232][233][234][235][236][237][238][239] In a representative example, Sun et al studied the degradation process of 17β-estradiol (E2) driven by enzyme-like MnO 2 particles in detail. 236 With the presence of humic acid (HA), four pathways of E2 transformation were revealed, including decomposition, homo-coupling, dehydrogenation, and hetero-coupling (Fig.…”
Section: Degradation Of Phenolic Pollutantsmentioning
confidence: 99%
See 1 more Smart Citation